Karakteristik organoleptik dan nilai gizi biskuit dengan fortifikasi tepung surimi ikan swanggi (Priacanthus tayenus): Organoleptic and nutritional characterization of fish biscuits with fortification of surimi powder from purple-spotted bigeye fish (Priacanthus tayenus) - Ika Astiana; Almira Fardani Lahay; Siluh Putu Sri Dia Utari; Iftachul Farida; Pinky Natalia Samanta; I Gusti Ayu Budiadnyani; Desy Febrianti (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2023)
Fish have high nutritional value, but most people do not consume fish because they have a fishy smell, many thorns, and are prone to rottenness. Therefore, the diversity of processed seafood could be a solution for people who do not like to consume fish. This study aimed to determine the effect of the formulation on the level of consumer acceptance and to determine the nutritional value of biscuits fortified with surimi powder. The research method was divided into three steps: surimi characterization, fish biscuit formulation, and fish biscuit characterization. The concentrations of surimi powder used were 0%, 10%, 20%, 30%, 40%, and 50%. The data from this study were analyzed using the one-way ANOVA test with the Duncan advanced test for the organoleptic test and the Tukey advanced test for the proximate test, with a confidence level of 95%. Based on the results of the proximate test, fish surimi had a protein content of 19.91%, lipid content of 0.7%, ash content of 0.41%, water content of 78.9%, and carbohydrate content of 0.08%. Surimi powder had a protein content of 53.01%, lipid 5.03%, ash 1.35%, water 25.22%, and carbohydrate 15.39%. The best biscuit formulation was the fortification of surimi powder with a concentration of 20% with the results of the best preference test of appearance 7.50; smell 6.87; taste 7.37; and texture 7.13 from the maximum scale of 9 while the results of the proximate test with values of protein, lipid, mineral, water, and carbohydrate content of 16.91%; 17.10%; 2.80%; 5.67%; and 57.52%